Multi-Generation Model of Immigrant Earnings: Theory and Application - Gil S. Epstein; Tikva Lecker (Bar-Ilan University, Department of Economics, 2001)
The literature, starting with Chiswick (1977, 1978) to Gang and Zimmermann (2000), more recently, focuses on the economic achievements and performance of first- and second-generation migrants. This paper presents a three-generation migrant analysis, comparing relative economic performance of various migrant generations to one another and to the native population. We developed a theoretical model, which was then explored empirically using data from the 1995 Israeli Census. In both the theoretical and empirical analyses, the curve describing intergenerational immigrant earnings mobility is inversely U-shaped. The second generation earns relatively more than the first and third generations, while the third generation earns less than the second, but more than the first. Thus, assimilation of the third generation into the local population is far from clear.
Keywords: F22; 330; Intergenerational earnings mobility; migration; labor market performance